USING EMOJI PICTURES TO STRENGTHEN THE IMMUNITY OF PASSWORDS AGAINST ATTACKERS - Mohammed A. Fadhil Al-Husainy; Raghda Ahmed Malih (European Scientific Journal, ESJ, 2015)
User authentication is an essential step in information security. Textual passwords are the most traditional ways used in most user authentication systems to achieve the security of information, but textual passwords are vulnerable to many types of attacks such as: dictionary attacks, shoulder surfing, and spyware. Graphical password can overcome the shortcomings of the textual passwords, but it still vulnerable to shouldersurfing attacks, takes much space in the system and sometimes user takes a long time to enter. By using Emoji-pictures, a new technique that overcomes the drawbacks of both textual and graphical passwords was presented in this paper. The proposed technique is resistant to dictionary attacks, shoulder surfing, and spyware in addition to that it doesn't take large space in the system's database and provides a safe and enjoyable session for users during entering the password.